IMPROVEMENT OF TIGER BARB QUALITY (Puntiustetrazona) USING DIFFERENT DOSAGE OF CARROT FLOUR - Irwin Sukhairi; Rusliadi Rusliadi; Usman M. Tang (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT The purpose of this study was to determine the effect of adding carrot flour (Daucuscarrota L) to artificial feed on the brightness of the color of Tiger barb. The method used in this study is the experimental method using a completely randomized design (CRD) of 1 factor with 4 levels of treatment, and 3 replications.The dose of carrot flour in this study was 0% (control), 5%, 10%, 15%. The feed was tested on Sumatran fish measuring ± 3 cm long which was maintained in an aquarium measuring (30x40x40) cm3. The parameters measured include the brightness of the color, growth, survival, and water quality. The results showed that the addition of carrot flour to feed can increase the color of Tiger barb. The best dose is 15% which can increase the brightness of color 3.53, absolute weight growth of 0.54 grams, and growth of absolute length of 0.65 cm. Keywords : Puntiustetrazona, Carotenoid, Carrot flour, Feed